Architecture and Research Corpus Indexation of Texts by Yuri Shevelyov - Danyliuk, Illia; Zahnitko, Anatolii; Sytar, Hanna (Ñemitỹrã, 2023)
The article is devoted to the problem of creating a corpus of texts by Yuri Shevelyov. The main structural components of the text’s corpus have been determined, the functions have been singled out, the features of its filling have been characterized, extralinguistic and linguistic marking has been explained.